Poverty and its Alleviating Strategies among Rural Farming Households in Benue State, Nigeria - Upev, Samuel; Michael, Amurtiya; Mshelia, Shuaibu; Onu, Justice (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2021)
The study analysed rural farming households’ poverty status and alleviating strategies in Benue State, Nigeria. The specific objectives of the study were to: describes the rural household heads’ socio-economic characteristics; determine the poverty status of the respondents and its determinants; and identify poverty alleviating strategies of the respondents. Data for the study was collected from 420 respondents selected using a multi-stage sampling technique. Data collected were analysed using descriptive statistics, the Foster-Greer-Thorbecke poverty measurement index, and the Binary Logistic regression model. The findings of the study revealed a very high incidence of poverty (70%), having a gap of 0.34, and severity of 0.17. Poverty in the area is positively associated with the age of the household head and household size, while gender, educational level, off-farm activity, membership of a group, farm size, and land ownership are negatively associated with poverty. The common poverty alleviation strategies identified were agricultural wage labour (48.6%), rental services (45.0%), and transportation business (36.7%). Therefore, it was recommended that the government and other stakeholders should initiate sustainable social protection schemes that can assist rural residents in alleviating poverty until their condition improves.